2012
DOI: 10.1590/s0103-166x2012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida, cognição e desempenho nas funções executivas de idosos

Abstract: A relação entre qualidade de vida e funções cognitivas em idosos tem sido pouco estudada. O objetivo deste estudo foi examinar a associação entre qualidade de vida, cognição e desempenho nas funções executivas de idosos. O estudo teve a participação de 88 idosos. Utilizou-se o método amostral de conveniência. Todos os participantes responderam sobre condições sociodemográficas, qualidade de vida (World Health Organization Quality of Life Group-Bref), funções cognitivas (Mini-Exame do Estado Mental e Instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 13 publications
(12 reference statements)
2
24
0
16
Order By: Relevance
“…They also tend to engage in inadequate social behavior and experience progressive difficulty in dealing with emotional issues. 35 These observations were confirmed in a study conducted by Beckert et al, 24 whose results showed that better emotional control leads to a better cognitive performance in certain tasks.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…They also tend to engage in inadequate social behavior and experience progressive difficulty in dealing with emotional issues. 35 These observations were confirmed in a study conducted by Beckert et al, 24 whose results showed that better emotional control leads to a better cognitive performance in certain tasks.…”
Section: Discussionmentioning
confidence: 69%
“…32 Cognitive function is a determinant for the maintenance of an independent lifestyle and its loss is considered an indicator of decline and physical/functional weakness, which affect the individual's ability to perform activities of daily living. 24 Therefore, the results found for the dimension functional capacity could be explained by the degree of cognitive skills that the individual´s daily work and domestic activities demand, for which they require reason, spatial and temporal awareness, a healthy memory and communication skills. Activities of daily living are limited when these skills begin to decline.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some researchers found a positive relationship between cognitive function and quality of life (Beckert, Irigaray, & Trentini, 2012) and others argue that the more severe the cognitive impairment, the lower the quality of life (Leite et al, 2012a;Leite, Winck, Hildebrandt, Kirchner, & Silva, 2012b). Similarly, the findings of Winocur et al (2007) support the hypothesis that quality of life contributes to successful aging, more specifically, it contributes to preserve cognitive function.…”
Section: Discussionmentioning
confidence: 83%
“…Com base em estudos epidemiológicos a prevalência de alterações cognitivas, como a demência, varia de 1,6%, entre pessoas com idade de 65 a 69 anos, e 38,9% para pessoas com idade superiores há 84 anos, dados esses referentes à população brasileira 2 . Os declínios cognitivos podem acarretar modificações físicas, sociais e emocionais, bem como prejuízos da memória, podendo este ocasionar desde pequenos esquecimentos até severos comprometimentos 3 . Assim, alterações cognitivas podem comprometer a qualidade de vida dos idosos em vários aspectos funcionais e predispõe ao surgimento de diversas patologias, como a doença de Alzheimer que reflete diretamente na memória 4 .…”
Section: Introductionunclassified